2010
DOI: 10.1001/jama.2010.675
|View full text |Cite|
|
Sign up to set email alerts
|

Viral Etiology of Severe Pneumonia Among Kenyan Infants and Children

Abstract: In a sample of Kenyan infants and children admitted with severe pneumonia to a rural hospital, RSV was the predominant viral pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
260
6
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(317 citation statements)
references
References 29 publications
47
260
6
1
Order By: Relevance
“…PIV, hMPV, and RSV were associated with high relative risks for ARI and were only rarely detected in control subjects, which is concordant with previous studies. 11,17 These viruses all seem to be rapidly cleared from the respiratory tract after an infection, making qPCR a suitable diagnostic method. 8 Interestingly, hMPV was associated with severe disease presentations such as fever, decreased O 2 saturation, increased respiratory rate, and tachycardia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIV, hMPV, and RSV were associated with high relative risks for ARI and were only rarely detected in control subjects, which is concordant with previous studies. 11,17 These viruses all seem to be rapidly cleared from the respiratory tract after an infection, making qPCR a suitable diagnostic method. 8 Interestingly, hMPV was associated with severe disease presentations such as fever, decreased O 2 saturation, increased respiratory rate, and tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…7 Sensitive methods, such as quantitative real-time polymerase chain reaction (qPCR) analyses on nasopharyngeal samples, for a number of viruses have been introduced in the clinic as a sensitive diagnostic tool among children with respiratory tract infection. 8 However, whereas detection of some viruses, such as influenza virus and respiratory syncytial virus (RSV), clearly is predictive for respiratory disease, [9][10][11] the clinical significance upon detection of several other viruses needs further investigation. The interpretation of a viral detection is complicated by the fact that infections with multiple viruses are common in children with ARI and that many viruses have lately been reported to be found also in asymptomatic children.…”
mentioning
confidence: 99%
“…Studies have shown that respiratory viruses can be detected in up to 36% of samples from asymptomatic children. 33,34 Another contradiction in the literature was the association of the HRV C strain with severe cases. 4,5 Some of the HRV samples we sequenced belonged to the C strain.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] There are recent studies that also used molecular techniques to identify viral pathogens in lower respiratory infections (LRTI) in infants in sub-Saharan Africa, although they do not specifically report by infant HIV-infection and feeding strategy . [31][32][33][34][35][36][37][38] Several studies found that RSV was the most frequent pathogen, particularly in infants under 1 year. 35,36 Our study, and one from Mozambique, 34 found that adenovirus and rhinovirus were the two most common viral potential pathogens and were commonly found together in infants with pneumonia.…”
Section: Discussionmentioning
confidence: 99%